Familial amyloidotic polyneuropathy: a literature review - Monteiro, Beatriz Rezende; Fonseca-Neto, Olival Cirilo Lucena da (Brazilian Journal of Transplantation, 2021)
Introduction: Amyloidosis is defined as a heterogeneous group of conditions of unknown etiology, and familial amyloidotic polyneuropathy is one of the existing hereditary forms. This mutation usually leads to a progressive sensorimotor and autonomic polyneuropathy, which can present both sporadic and familial cases. Clinical spectrum is quite variable, as it is the severity of amyloid deposits. Liver transplantation and Tafamidis are the major therapeutic options available in Brazil. Purpose: To reinforce the most important aspects of a condition as heterogeneous as FAP further to also reviewing the possible therapeutic options according to the stage of the disease. Methods: The literature on PUBMED from January 2015 to December 2019 was reviewed by using the combination of descriptors Familial amyloid neuropathy AND Liver transplantation AND Treatment. RESULTS: FAP is a systemic and progressive condition of hereditary nature, caused by a mutation in the TTR gene with Val30Met being the most commonly found variation. Amyloid deposits start long before the onset of the clinical picture, as in other neurodegenerative diseases. FAP symptoms can vary according to the genetic mutation and the organs involved, with the heart and peripheral nerves being the main ones. The classic heel disease phenotype is characterized by neuropathy, predominantly in small fibers with dissociated sensory loss, added to early autonomic involvement and a positive family history. In Brazil, the time between the onset of the first symptoms and the FAP diagnosis is 5.9 years, which is an obstacle to optimizing the management of the disease. The approach of FAP requires a multidisciplinary care with a symptomatic approach, anti-amyloidosis and other specific therapies in case of cardiac, ocular, gastrointestinal and renal involvement. Liver transplantation has been associated to a positive long-term prognosis in patients in early disease stages, young people, good nutritional status, short disease duration, and with the Val30Met variation. Conclusion: Nowadays, despite the fact that FAP is an incurable disease, it is possible to control its progression through early recognition and diagnosis associated to the initiation of an appropriate therapy. A multidisciplinary approach must always be carried out and therapeutic strategies must go beyond anti-amyloidotic therapy.